Morphology and distribution of suspended particles during typhoon-induced algal bloom in the Pearl River Estuary - Lin, Yaokun; Ye, Leiping; Li, Chao; Cui, Yongsheng; Wu, Jiaxue (Frontiers in Marine Science, 2024)
Suspended particles, including plankton and clay minerals, are ubiquitous in aquatic environments. Understanding their characteristics is crucial for gaining insights into biogeochemical processes and accurately assessing material and element fluxes in coastal estuaries. Following the impact of Typhoon Cempaka on the Pearl River Estuary (PRE) in July 2021, we conducted field observations throughout various stages of the subsequent algal bloom, simultaneously capturing holographic images of particles alongside hydrographic data. We developed an innovative method to transform these images into datasets for deep learning object detection models, enabling advanced morphological analysis. This approach allowed for efficient identification and characterization of particle morphology and vertical distribution in coastal estuarine environments. Our study revealed substantial morphological and distributional differences in diatoms and aggregates in response to environmental changes throughout the stages of the typhoon-induced algal bloom. Specifically, elongated-curled diatoms tended to settle in the middle and bottom layers under turbulent mixing but remained concentrated in the surface phytoplankton layer under stratified conditions. In contrast, short-straight diatoms exhibited minimal sensitivity to physical dynamics, persisting in the surface layer across all conditions. We observed that aggregate morphology and distribution patterns correlated with physical dynamics intensity and diatom concentration. These findings accurately reflect particles’ natural states and underscore the potential of in situ particle morphology and distribution as indicators of environmental changes, highlighting the ecological significance of studying in situ particle functional traits. We recommend that future studies expand particle imaging across diverse conditions to deepen understanding of estuarine ecosystem evolution.